Le front pionnier agro-désertique égyptien, par-delà rural et ruralité ? - Delphine Acloque (EchoGéo)
Since the middle of the 20th century, desert margins have become the place where the future of the Egyptian agriculture is projected, both by the state and by international institutions. This article sheds light on the nature of the new agro-desert territories and shows how the frontier questions the very categories of rural and rurality. We discuss how this expanding agricultural sector and its diversity of stakeholders (from small peasants to large companies) are spatially embedded in desert areas. To what extent the analysis of the Egyptian agricultural frontier should go beyond the concept of rurality? What socio-spatial categories should be used and built to characterize the new territories?